Central motor conduction is abnormal in motor neuron disease. Issue 2 (February 1987) - Ingram, D A; Swash, M
Abstract : Conduction in the central motor pathways of the brain and spinal cord was studied in 12 patients with motor neuron disease. Six healthy volunteers served as controls. Transcutaneous electrical stimulation of the cortex, cervical cord, thoracic cord and conus medullaris was used to determine motor latencies to the biceps brachii, thenar eminence and tibialis anterior muscles. Prominent, and often asymmetrical, slowing of central motor conduction was demonstrated in seven of the 12 patients; these findings were most marked in the spinal cord and in most cases correlated with clinical features of corticospinal involvement. In general it was more difficult to excite motor pathways in the central nervous system in the patients with motor neuron disease than in control subjects. Evidence of subclinical involvement of central motor pathways was found in five patients. The central lesion in motor neuron disease may thus contribute more significantly to the clinical deficit than has been realised, since the clinical signs of the upper motor neuron lesion are often masked by the more obvious lower motor neuron features.